"Venus I". - Verlinden, Jan; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1988)
Bekaert, Piet ; Buytaert, Jan ; Goezu, André ; Goldmann, Jean ; Janssens, Michel ; Leclercq, Guy ; Lens, Gilbert ; Van Akelijen, Roger ; Vansteelandt, Rita ; Van Wijnendael, Silvain ; Vreven, Flor
"Venus I", Hof ter Nederloo, Sint-Pieters-Leeuw, 9 september - 16 oktober 1988
boek